Photothermal-triggered immunogenic nanotherapeutics for optimizing osteosarcoma therapy by synergizing innate and adaptive immunity. (March 2022) - Liu, Kaiyuan; Liao, Yuxin; Zhou, Zifei; Zhang, Li; Jiang, Yingying; Lu, Hengli; Xu, Tianyang; Yang, Dong; Gao, Qiuming; Li, Zihua; Tan, Shuo; Cao, Wentao; et al.
Abstract: Inadequate immune response remains a critical cause of immunotherapy failure in various tumor treatments. Herein, we offer a new approach to achieve a cross-talk between innate and adaptive immune responses based on a new nanoplatform for photothermal therapeutics. The nanoplatform was formed by linking titanium carbide MXene with Mn 2+ -contained ovalbumin (OVA), where it can trigger efficient mt-DNA presentation and the release of OVA and Mn 2+ upon the irradiation of near-infrared laser. More importantly, the released mt-DNA and Mn 2+ synergistically activate innate immunity via the cGAS-stimulator of the interferon genes signaling pathway, and the OVA and protein antigens from tumor cells enhance adaptive immunity. Furthermore, in an osteosarcoma model, we observed that the proposed nanoplatform leads to the effective presentation of tumor antigens, which boost the maturation of dendritic cells (DCs) to the hilt and thus improve the infiltration of cytotoxic T lymphocyte in primary and distant tumors. Collectively, our work not only demonstrates a method for constructing a new nanoplatform for photothermal therapeutics but also provides a general strategy for synchronously activating innate and adaptive immunities to promote the maturation of DCs for antimetastasis tumor therapy. Graphical abstract: Upon irradiation, tumor-derived antigen and mt-DNA release from dying tumors which recruits the DCs in situ. And TPOM NPs decompose into Mn 2+ and OVA under NIR. Immature DCs (iDCs) would uptake the OVA and antigen which promote DCs maturation through the adaptive immunity. MtDNA and Mn 2+ could stimulate innate immune response in iDCs by upregulating STING pathway to get activation. Eventually iDC cells transformed into mature DCs to activate T lymphocytes for anti-tumor and anti-mestastic immunotherapy. Image 1